2020
DOI: 10.1158/1078-0432.ccr-19-3102
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Hsp90 Inhibitor Selectively Radiosensitizes HNSCC and Pancreatic Xenografts

Abstract: Purpose: Treatment approaches using Hsp90 inhibitors at their maximum tolerated doses (MTDs) have not produced selective tumor toxicity. Inhibition of Hsp90 activity causes degradation of client proteins including those involved in recognizing and repairing DNA lesions. We hypothesized that if DNA repair proteins were degraded by concentrations of an Hsp90 inhibitor below those required to cause nonspecific cytotoxicity, significant tumor-selective radiosensitization might be achieved.Experimental Design: Tand… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 36 publications
3
10
0
Order By: Relevance
“…Importantly, HSP90i by NW457 significantly reduced the clonogenic survival upon irradiation in both cell lines ( Figure 1E ), confirming our hypothesis that multi-target interference with DDR function by HSP90i at per se non-toxic doses suffices to sensitize resistant GBM cells to irradiation. Similar findings were very recently reported for other cancer entities ( 62 , 63 ). Morphologically, the mode of cell death underlying reduced clonogenic survival upon HSP90i plus radiation was a highly disruptive, necrotic one which occurred after several rounds of aberrant mitosis and intermediate states of highly aneuploid cells with multiple and/or giant nuclei ( Supplementary Movie File 1 ) ( 64 ).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Importantly, HSP90i by NW457 significantly reduced the clonogenic survival upon irradiation in both cell lines ( Figure 1E ), confirming our hypothesis that multi-target interference with DDR function by HSP90i at per se non-toxic doses suffices to sensitize resistant GBM cells to irradiation. Similar findings were very recently reported for other cancer entities ( 62 , 63 ). Morphologically, the mode of cell death underlying reduced clonogenic survival upon HSP90i plus radiation was a highly disruptive, necrotic one which occurred after several rounds of aberrant mitosis and intermediate states of highly aneuploid cells with multiple and/or giant nuclei ( Supplementary Movie File 1 ) ( 64 ).…”
Section: Resultssupporting
confidence: 92%
“…In the present study, we report that treatment with very low concentrations of the pochoxime-derived HSP90 inhibitor NW457 which per se exhibit only limited cytotoxicity leads to DDR protein disintegration in GBM cells. We observed several key regulators of the DDR to be affected by HSP90i, previously published HSP90 client proteins as well as DDR regulators with so far unknown HSP90 dependence ( 32 , 54 56 , 62 ). The cluster with the strongest decrease in protein levels upon HSP90i treatment in human and mouse GBM cell lines comprised CHK1, RAD51, DNA2, and NHEJ1.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…These claims were evident in a recent publication from Mehta et al . [ 1 ]. For example, one expectation is that any new agent must show single-agent efficacy in the clinic before moving into advanced studies.…”
Section: First-in-class Drugs Versus Me-too Drugsmentioning
confidence: 99%
“…Mehta, et al used an Hsp90 inhibitor AT13387 (onalespib), which has shown exciting activity in clinical trials, but even at the MTD does not have an approvable efficacy profile [ 1 ]. AT13387 has certain interesting properties that make it relatively non-toxic at a therapeutic dose.…”
Section: Combination Study With At13387 and Radiationmentioning
confidence: 99%